Laparoscopic ischemic conditioning of the stomach prior to esophagectomy. Issue 5 (20th July 2012) - Yetasook, A. K.; Leung, D.; Howington, J. A.; Talamonti, M. S.; Zhao, J.; Carbray, J. M.; Ujiki, M. B.
Summary Several complications after esophagectomy with gastric pull‐up are associated with ischemia within the gastric conduit. The aim of this study is to assess the feasibility of laparoscopic ischemic preconditioning of the stomach prior to thoracotomy, esophagectomy, and gastric pull‐up with an intrathoracic anastomosis. A retrospective review of 24 consecutive patients between October 2008 and July 2011 with esophageal adenocarcinoma (stage I–III) undergoing laparoscopic gastric ischemic conditioning prior to esophagectomy was conducted. Conditioning included laparoscopic ligation of the left and short gastric arteries, celiac node dissection, and jejunostomy tube placement. Formal resection and reconstruction was then performed 4–10 days later. Of the 24 patients, 88% received neoadjuvant chemotherapy/radiation therapy. Twenty‐three of the 24 patients underwent successful laparoscopic ischemic conditioning and subsequent esophagectomy. Total mean number of lymph nodes harvested was 21.8 (±8.0), and a mean of 5.3 (±2.4) celiac lymph nodes identified. There were no conversions to an open procedure. Length of stay was 3.8 (±4.8) days with a median length of stay of 2 (1–24) days. Three patients experienced anastomotic leak, six patients experience delayed gastric emptying, and two patients developed anastomotic stricture. There were no surgical site infections. R0 resection was achieved in all patients who underwent laparoscopic ischemic conditioning followed by esophagectomy. Laparoscopic ischemic conditioning of the gastric conduit has been shown to be feasible and safe.